The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1161/atvbaha.107.153239
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Arterial Lipoprotein Lipase Expression Augments Inflammatory Responses and Impairs Vascular Dilatation

Abstract: Objective-Although epidemiologic data suggest that hypertriglyceridemia and elevated plasma levels of fatty acids are toxic to arteries, in vitro correlates have been inconsistent. To investigate whether increased endothelial cell expression of lipoprotein lipase (LpL), the primary enzyme creating free fatty acids from circulating triglycerides (TG), affects vascular function, we created transgenic mice that express human LpL (hLpL) driven by the promoter and enhancer of the Tie2 receptor. Methods and Results-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…In a second approach, we measured TRL margination in mice that express human LPL in endothelial cells [EC-hLPLH transgenic mice; (Takahashi et al, 2008)]. LPL is normally produced by myocytes in the heart and requires GPIHBP1 to move it across endothelial cells to the capillary lumen.…”
Section: Resultsmentioning
confidence: 99%
“…In a second approach, we measured TRL margination in mice that express human LPL in endothelial cells [EC-hLPLH transgenic mice; (Takahashi et al, 2008)]. LPL is normally produced by myocytes in the heart and requires GPIHBP1 to move it across endothelial cells to the capillary lumen.…”
Section: Resultsmentioning
confidence: 99%
“…Additional experiments using TEER (transendothelial electrical resistance) measurements showed that the resistance of the monolayer decreased following treatment with TGRL lipolysis products [166]. Recent studies in mice overexpressing hLpL (human LpL) have shown that excess vascular wall LpL augments vascular dysfunction in the setting of inflammation [176,177]. Furthermore, in transgenic mice expressing hLpL, agonist-induced contraction of smooth muscle cells was increased when compared with that of wild-type mice [178].…”
Section: Tgrl Lipolysis Products and Vascular Inflammationmentioning
confidence: 99%
“…Although the relative abundance of the HODEs was low and their potency was similar to that of their parent FAs, this study established that LpL lipolysate effects on endothelial cells were dependent on the released milieu of FAs, which included an array of oxylipins. TNF-α-induced infl ammation normally reduces LpL expression on the endothelium; however, when LpL is maintained, increased vascular cell adhesion molecule (VCAM) and E-selectin expression and impaired endothelium-dependent vasodilation are observed [39]. Coleman et al [40] demonstrated an LpL-dependent role for Cu 2+ -oxidized VLDL in activating adipocytes via PPARβ/δ, and simultaneously demonstrated the activation of PPARβ/δ by 13-HODE and 15-HETE.…”
Section: Lipoprotein Lipasementioning
confidence: 99%